Identification of wire electrical discharge machinability of SiC sintered using rapid hot pressing technique. Issue 11 (1st August 2020) - Singh, Meinam Annebushan; Joshi, Kamlesh; Hanzel, Ondrej; Singh, Ramesh Kumar; Šajgalík, Pavol; Marla, Deepak
Abstract: A rise in demand for silicon carbide in the semiconductor sector is often met with a setback due to the inability to machine them effectively. The high cost of the material further poses a significant challenge to reduce material losses during machining to a minimal level. Electrical discharge machining is an alternate approach that can machine various material regardless of the material's hardness, as long as they are electrically conductive in nature. The rapid hot press sintering technique is a material fabrication approach that relates to superior electrical and thermal characteristics without the addition of any additional fillers. Thus, the present work focuses on the fabrication of silicon carbide using rapid hot press sintering technique and subsequent identification of the influential parameters that best relates to a superior machining scenario in wire electric discharge machining. The effect of various process parameters (open voltage, servo voltage, pulse duration, wire speed, and wire tension) on the overall machining characteristics were carefully analyzed. The intensity of the discharge energy significantly influenced the crater formation on the workpiece surface, which directly affected the overall output characteristics. The variation in the concentration of discharge, open and arcing pulses with servo voltage resulted in varying output characteristics. A minimum kerf width of 165 μm was obtained in the current work with a wire electrode of diameter 150 μm, which considerably advances the step towards minimization of material loss. The detailed analysis of the machined surface suggested the removal of SiC by the combined action of melting, evaporation, and thermal spalling effect. Furthermore, the recast layer was observed to be porous due to severe oxidation and decomposition phenomena.